Polyfunkční dům Pod Spravedlností - Ferdan, Martin (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Předmětem diplomové práce je zpracování projektové dokumentace pro novostavbu polyfunkčního objektu. Novostavba se nachází v katastrálním území města Moravské Budějovice. Využití objektu spočívá ve dvou částech daného objektu. A část, která slouží pro administrativní účely a částí, která slouží pro bytovou část. Administrativní část se nachází v levé části stavebního objektu, bytová část v pravé části. Objekt je navržen jako tří a čtyř podlažní objekt, který je částečně podsklepený. Objekt je zastřešen plochými střechami. Objekt je založen na základových pasech z prostého betonu. Svislé nosné konstrukce nadzemních podlaží jsou navrženy z keramických tvárnic. Stropní konstrukce a schodiště navrženy vyztuženého betonu.

The subject of the diploma thesis is the processing of project documentation for new construction of a multifunctional building. The new building is located in the cadastral area the city of Moravské Budějovice. The use of the object consists of two parts object. And a part that is used for administrative purposes and a part that is used for housing part. The administrative part is located in the left part of the building, the residential part in the right part. The building is designed as a three- and four-story building, which is partially basement. The building is covered with flat roofs. The object is based on foundation belts made of plain concrete. Vertical supporting structures above ground floors are designed from ceramic blocks. Ceiling construction and stairs designed reinforced concrete.
Multifunctional building Pod Spravedlností
Keywords: Polyfunkční objekt; novostavba; keramické tvárnice; plochá střecha; multifunctional building; new building; ceramic blocks; flat roof